The Analysis of Relationship Between Parenting Pattern, Demographic Variables, Adversity Intelligence and Emotional Intelligence - Prasetio Rumondor; Syatria Adymas Pranajaya; Sudadi Sudadi; Sumarni Rumfot; Agus Rofi’i (Departement of Mathematics Education, 2023)
This study aims to determine the effect of emotional intelligence and parenting style on adversity intelligence. The population in this study were teenagers who attended junior and senior high schools in Jakarta. Testing the validity of the construct and statistical analysis of Structural Equating Modeling (SEM) obtained a fit model of the influence of emotional intelligence, parenting, and demographic variables on the role-influence of adversity-fit intelligence with empirical data. The results of the study show that the emotional intelligence variable evaluates other people's emotions; parenting style is not involved; and the demographic variables of gender and education level have a significant effect on adversity intelligence. Evaluation of other people's emotions has a negative direction towards adversity intelligence. That is, a high evaluation of other people's emotions has an impact on a low adversity quotient. As with uninvolved parenting, gender and education level have a positive relationship. This study aims to determine the effect of emotional intelligence and parenting style on adversity intelligence. The population in this study were teenagers who attended junior and senior high schools in Jakarta. Testing the validity of the construct and statistical analysis of Structural Equating Modeling (SEM) obtained a fit model of the influence of emotional intelligence, parenting, and demographic variables on the role-influence of adversity-fit intelligence with empirical data. The results of the study show that the emotional intelligence variable evaluates other people's emotions; parenting style is not involved; and the demographic variables of gender and education level have a significant effect on adversity intelligence. Evaluation of other people's emotions has a negative direction towards adversity intelligence. That is, a high evaluation of other people's emotions has an impact on a low adversity quotient. As with uninvolved parenting, gender and education level have a positive relationship.